The Handbook of Nonagency Mortgage-Backed Securities (Frank J. Fabozzi Associate, 2000)
Frank Fabozzi and Chuck Ramsey update their treatise on nonagency mortgage backed securities in this third edition of The Handbook of Nonagency Mortgage Backed Securities. Focused on an important investing area that continues to grow, this book provides comprehensive coverage of all aspects of this specialized market sector, including the mortgage-related asset-backed securities market and commercial mortgage-backed securities. There is information on raw products, such as jumbo loans, alternative A mortgages, and 125 LTV mortgages, as well as structured products, analytical techniques, prepayment characteristics, and credit issues. This fast-growing segment also includes nonagency pass through, nonagency collateralized mortgage obligations, home loan equity-backed securities, and manufacture housing loan backed securities